Assessing awareness on laboratory safety: a case study in Pahang, Malaysia - Nur Liyana Ali,; Goh, Choo Ta; Sharifah Zarina Syed Zakaria,; Sharina Abdul Halim,; Mazlin Mokhtar,; Lee, Khai Ern; Lubna Alam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Science education emphasises on obtaining knowledge, in which includes hands-on knowledge involving experiments conducted in laboratories. However, since experiments require interactions between students, substances, and equipment, laboratories that can pose great risks to users. In this regards, the Ministry of Education Malaysia has taken proactive approach to enhance laboratory safety via School Science Laboratory Management and Safety guidebook, textbooks, and science-based practical workbooks that are used throughout secondary schools in Malaysia. It is challenging to ascertain students’ awareness on laboratory safety throughout Malaysia, hence this study selected 8 secondary schools located in Pahang as case study to determine students’ awareness on laboratory safety. A questionnaire was developed by focusing on five components, namely work procedure, safety equipment, handling experiments, chemical waste management, and emergency response plan, and then the questionnaire was completed by 558 science stream students from schools located at urban and rural areas. The results of this study indicate that the overall level of students’ awareness on laboratory safety is at medium-high level, and this has shown that the existing measures in secondary school to enhance awareness of laboratory safety is adequate. Nevertheless, there are still room for improvement to further enhance students’ awareness on laboratory safety in Malaysia.